Pengaruh CSR terhadap Kebahagiaan Karyawan dan Kinerja Perusahaan di PT. Indofood - Akhmad Shofuwan Nuvail; Masiyah Kholmi (CV. Creative Tugu Pena, 2024)
This study aims to explore the influence of CSR on employee happiness and company performance at PT Indofood. The method used in this research is a literature study, where data is collected from various literatures, including books, journals, and articles that discuss CSR and its impact on companies. Through a comprehensive CSR program, including initiatives such as Indofood Riset Nugraha, this study found that employee involvement in social activities conducted by the company can increase their sense of ownership and job satisfaction. The results show that employees who feel valued and involved in CSR programs tend to show higher loyalty, as well as better productivity. In addition, there is a positive influence of CSR on company performance, which is reflected in an improved corporate image and Net Profit Margin (NPM). This finding confirms the importance of CSR integration in PT Indofood's business strategy to achieve sustainability and long-term growth. Thus, CSR not only provides benefits to society but also strengthens relationships with employees, creating a more positive and productive work environment.